Apoyo en la Supervisión Técnica de la Construcción del Puente el Pindal en el Municipio de San Bernardo del Departamento de Nariño (2021)
In this document, the work carried out as an intern in the Municipal Mayor's Office of San Bernardo in the Department of Nariño is presented, which was motivated by the entity's need to recruit civil engineering interns to satisfy the shortcomings that the office of works secretariat in support staff to carry out supervision activities to the public works contracts hired by this entity. The main objective of the development of this internship was to be able to provide technical support in the supervision of the construction of the El Pindal bridge that connects the municipality of San Bernardo with the Municipality of San Pedro de Cartago in the Department of Nariño. This work was carried out obtaining excellent results since the contract in execution is being developed, complying with the plans and technical specifications proposed for the correct outcome of the project.